STREET SWEEPER - RAM, B.SURESH; BABU, P.MAHESH; KIRAN, K.RAVI; REDDY, V.HARIKA; MANOHAR, E. (The journal of contemporary issues in business and government, 2022)
The main aim of our project is to help the GHMC sweepers. Sweepers play an important role in maintaining the health and hygiene within the cities. Sweepers are the vulnerable segment of our community and suffering from different occupational health problems due to limited education, lack of knowledge on occupational health hazards. The problems include the hand pain, back pain, shoulder pain etc. So, to overcome this problem we our team planned to help those workers by introducing the machine called street sweeper. This machine is very helpful to them which reduces their time, energy and make their work simple and in an easy manner. This machine is easy to handle and affordable by them. The street sweeper Machine is hardware-based project. The cleaner solves the problem of dusty roads, choked pipelines and manholes, removal of metal particles from road and also obstacles. In this project an efforts has been made to develop a mechanically operated eco-friendly road sweeping machine so that it can be used for small space cleaning without pollution. On other hand in rural area the road cleaning is done by an manual operated which can be hazards to health like asthma, bronchitis etc to the worker. the cost of mechanically operated sweeping machine is less as compare to electric operated sweeping machine and the machine is economical and comfortable for operating in rural area and it is suitable on small spaces, it is eco-friendly to user. our motive is to present a detailed qualitative study of cleaning system using the cleaner, the main focus being cleanliness with minimum utilization of resources available with us.